The Role of Tuberculosis Cadres in the Tuberculosis Control Program in Medan City - Nur Asiyah Nasution; Lita Sri Andayani; Kintoko Rochadi Rochadi (Berita Kedokteran Masyarakat (BKM), 2020)
Background. North Sumatra Province is included in the top seven provinces in Indonesia with a high TB incidence rate. Prevalence of pulmonary TB based on a doctor's diagnosis history of 0.30%, Case Notification Rate (CNR) for smear pulmonary TB is 104.3 per 100,000, success rate of treatment (SR) reached 91.31 percent. The percentage of TB cure in 2017 of 82.40 percent, is considered to be lower compared in 2016 of 85.52 percent. Purpose. The purpose of study was to analyze the role of TB cadres in TB control programs in Medan City. Method. This research was an observational analytic with a cross sectional approach. The population in this study were all cadres in Belawan Health Center (25 cadres), Helvetia Health Center (28 cadres), Amplas Health Center (24 cadres), Glugur Darat Health Center (24 cadres) and Sering Health Centre (24 cadres) totaling 125 cadres. Result. There is an influence of knowledge, attitudes and actions of Tuberculosis cadres on the role of Tuberculosis cadres. The results of multivariate analysis of knowledge with p = 0.014, attitude with p = 0,001, actions with p = 0.010. Conclusion. Behavioral factors, namely cadre attitudes become the dominant factor influencing the role of TB cadres with p = 0.014 and Exp (B) = 14.651. Suggested to health center do coaching and training, and position cadres as partners.